Same beach, next year [large type] : a novel - Frank, Dorothea Benton (HarperLuxe, an imprint of HarperCollins Publishers, 2017)
A chance meeting on the Isle of Palms, one of Charleston's most stunning barrier islands, brings former sweethearts Adam Stanley and Eve Landers together again. Their respective spouses, Eliza and Carl, fight sparks of jealousy flaring from their imagined rekindling of old flames. As Adam and Eve get caught up on their lives, their partners strike up a deep friendship -- and flirt with an unexpected attraction -- of their own. Year after year, Adam, Eliza, Eve, and Carl eagerly await their reunion at Wild Dunes, a condominium complex at the island's tip end, where they grow closer with each passing day, building a friendship that will withstand financial catastrophe, family tragedy, and devastating heartbreak. The devotion and love they share will help them weather the vagaries of time and enrich their lives as circumstances change, their children grow up and leave home, and their twilight years approach.